Outcomes of Adults With Relapsed/Refractory Acute Myeloid Leukemia Treated With Venetoclax Plus Hypomethylating Agents at a Comprehensive Cancer Center - Tenold, Matthew E.; Moskoff, Benjamin N.; Benjamin, David J.; Hoeg, Rasmus T.; Rosenberg, Aaron S.; Abedi, Mehrdad; Tuscano, Joseph M.; Jonas, Brian A. (Frontiers in Oncology, 2021)
Relapsed/Refractory acute myeloid leukemia (AML) is a devastating disease with a poor prognosis and represents a major unmet medical need. In November 2018, the B-Cell-Lymphoma-2 inhibitor venetoclax, in combination with hypomethylating agents, was initially approved for the frontline treatment of AML in elderly patients or patients who are ineligible for induction chemotherapy, and these combinations have had a major impact on the AML treatment landscape. We report on a real-world academic center experience of treating 25 patients with relapsed/refractory AML using venetoclax in combination with decitabine or azacitidine, which is not otherwise widely evaluated in the current literature. We observed an overall response rate of 52%, with 8 patients (32%) achieving composite complete remission. Median overall survival was 5.5 months, and for patients achieving composite complete remission this was 21.6 months. One-year estimated overall survival was 38%. Three patients were able to proceed directly to stem cell transplant for consolidation, and all 3 were alive at last follow-up, ranging 13.8-24.0 months. We found venetoclax in combination with hypomethylating agents to be well tolerated and potentially efficacious in securing long-term remissions for patients with relapsed/refractory AML.